2020
DOI: 10.1111/bdi.12980
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress parameters and antioxidants in patients with bipolar disorder: Results from a meta‐analysis comparing patients, including stratification by polarity and euthymic status, with healthy controls

Abstract: Objective To investigate oxidative stress markers and antioxidants in bipolar disorder (BD). Methods Electronic MEDLINE/PubMed/Cochrane‐Library/Scopus/TripDatabase search until 06/30/2019 for studies comparing antioxidant or oxidative stress markers between BD and healthy controls (HCs). Standardized mean differences (SMD) and 95% confidence intervals (CIs) were calculated for ≥3 studies. Results Forty‐four studies (n = 3,767: BD = 1,979; HCs = 1,788) reported on oxidative stress markers malondialdehyde (MDA),… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 72 publications
6
37
0
Order By: Relevance
“…Thus, even patients who had been diagnosed recently (≤ 3 years of the disease), had a strong increase of TBA-RS levels and CAT activity, demonstrating that the oxidative stress that started in the initial phases was maintained 36 . Our results have many similarities when we compare the results of a large meta-analysis carried out by 37 . They analyzed 44 studies, which included 1979 bipolar patients and 1788 healthy control patients, evaluating the following oxidative stress markers: SOD, CAT, GSH-Px enzymes, and TBA-RS levels during different phases of the disease (mania, depression, and euthymia), and separated them into subgroups (use and non-use of mood-stabilizing drugs).…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Thus, even patients who had been diagnosed recently (≤ 3 years of the disease), had a strong increase of TBA-RS levels and CAT activity, demonstrating that the oxidative stress that started in the initial phases was maintained 36 . Our results have many similarities when we compare the results of a large meta-analysis carried out by 37 . They analyzed 44 studies, which included 1979 bipolar patients and 1788 healthy control patients, evaluating the following oxidative stress markers: SOD, CAT, GSH-Px enzymes, and TBA-RS levels during different phases of the disease (mania, depression, and euthymia), and separated them into subgroups (use and non-use of mood-stabilizing drugs).…”
Section: Discussionsupporting
confidence: 53%
“…Thus, when Jiménez-Fernández et al, (2020) 37 compared healthy controls with euthymic medicated bipolar patients in their meta-analysis, they had the following results: CAT activity scores (p <0.02), TBA-RS levels (p <0.0001), and without differences relating to SOD activity (p = 0.10), and the GSH-Px activity (p = 0.40). These are the same as those observed in our research, even when we divide the patients into two groups with (≤ 3 years and ≥ 10 years of the disease), with an increase in CAT activity (≤ 3 years p < 0.0001; ≥ 10 years p < 0.0001) and TBA-RS levels (≤ 3 years p < 0.0001; ≥ 10 years p < 0.0001) and with no signi cant difference relates SOD activity (≤ 3 years p = 0,9; 10 years p = 0.3), and GSH-Px activity (≤ 3 years p = 0.8; ≥ 10 years p = 0.3) see Fig.…”
Section: Discussionmentioning
confidence: 97%
“…TBARSs, carbonyl proteins, malondialdehyde (MDA), and nitrites have also been used as peripheral markers of OS. Additional antioxidant markers include total antioxidative capacity; measures of antioxidants (glutathione, zinc, and uric acid); as well as levels of SOD, GPX, and glutathione S-transferase [94,112]. A study of 113 BD patients who were euthymic and 78 controls found decreased TBARS, MDA, and total antioxidative capacity levels in the BD patients compared with the controls [94].…”
Section: Oxidative Damage In Bdmentioning
confidence: 99%
“…A systematic review pointed out that uric acid level may be a potential biomarker of aggressive behavior in patients with BD [32].Irritability is the core symptom of BD patients.Liu's study on Chinese Han population shows that the uric acid level of BD patients is higher than that of healthy controls matched with their age and gender [33].Elif Tatlıdil Yaylacı found that the uric acid level of BD type I remission was higher than that of RDD remission and HC group, and the uric acid level of RDD group was lower than that of HC group [14].Our results show that the level of uric acid in BD group is still higher than that in RDD group at the time of depression, which plays a supplementary role in the above research and provides evidence for UA as a biomarker for the differential diagnosis of BD.…”
Section: Discussionmentioning
confidence: 99%